Zbiorem rozwiązań nierówności 3x2+2x−1≤0 jest
A. (−∞,−1)∪⟨13,+∞)
B.(−1,13)
C.(−∞,−1)∪(13,+∞)
D.⟨−1,13⟩



Odpowiedź :

Cześć!

Rozwiązanie nierówności

[tex]3x^2+2x-1\leq0\\\\a=3, \ b=2, \ c=-1\\\\\Delta=b^2-4ac\rightarrow2^2-4\cdot3\cdot(-1)=4+12=16\\\\\sqrt{\Delta}=\sqrt{16}=4\\\\x_1=\frac{-b-\sqrt{\Delta}}{2a}\rightarrow\frac{-2-4}{2\cdot3}=\frac{-6}{6}=-1\\\\x_2=\frac{-b+\sqrt{\Delta}}{2a}\rightarrow\frac{-2+4}{2\cdot3}=\frac{2}{6}=\frac{1}{3}\\\\\huge\boxed{x\in\langle-1;\frac{1}{3}\rangle}[/tex]